Entrepreneurial competency training instructor's manual - Diaz, Paz H. (EDCEL, PACSB, SERDEF, and U.P. ISSI, 1993)
A manual which aims to guide the intructor in teaching entrepreneurial competency in the Philippines. Intended for the use of teachers and instructors of entrepreneurship.